Breast cancer metastases to the thyroid gland – an uncommon sentinel for diffuse metastatic disease: a case report and review of the literature - Agata M. Plonczak; Aimee N. DiMarco; Roberto Dina; Dorothy M. Gujral; Fausto F. Palazzo (Journal of Medical Case Reports, 2017)
Abstract Background Metastases to the thyroid are rare. The most common primary cancer to metastasize to the thyroid is renal cell carcinoma, followed by malignancies of the gastrointestinal tract, lungs, and skin, with breast cancer metastases to the thyroid being rare. Overall, the outcomes in malignancies that have metastasized to the thyroid are poor. There are no prospective studies addressing the role of surgery in metastatic disease of the thyroid. Isolated thyroidectomy has been proposed as a local disease control option to palliate and prevent the potential morbidity of tumor extension related to the airway. Here, we present a case of a patient with breast cancer metastases to the thyroid gland and discuss the role of thyroidectomy in the context of the current literature. Case presentation A 62-year-old Afro-Caribbean woman was diagnosed as having bilateral breast carcinoma in 2004, for which she underwent bilateral mastectomy. The pathology revealed multifocal disease on the right, T2N0(0/20)M0 grade 1 and 2 invasive ductal carcinoma, and on the left side, T3N1(2/18)M0 grade 1 invasive ductal carcinoma. Surgery was followed by adjuvant chemotherapy and regional radiotherapy. The disease was under control on hormonal therapy until 2016, when she developed cervical lymphadenopathy. The fine-needle aspiration cytology of the thyroid was reported as papillary thyroid cancer; and the fine-needle biopsy of the left lateral nodal disease was more suggestive of breast malignancy. She underwent a total thyroidectomy and a clearance of the central compartment lymph nodes and a biopsy of the lateral nodal disease. The histopathological analysis was consistent with metastatic breast cancer in the thyroid and lymph nodes with no evidence of a primary thyroid malignancy. Conclusions A past history of a malignancy elsewhere should raise the index of suspicion of metastatic disease in patients presenting with thyroid lumps with or without cervical lymphadenopathy. Detection of metastases to the thyroid generally indicates poor prognosis, obviating the need of surgery in an already compromised patient. An empirical thyroidectomy should be considered in select patients for local disease control.